The Last Lick: A Lived Experience of Non-incarcerated Partners - Adetunji, Christian Matthew; Gathoni, Anne Wambugu; Kamau, Elizabeh Wangui (European Scientific Journal, ESJ, 2023)
The incarceration of their partners has a profound effect on them and affects them differently from other family members. But what are these effects, and what are the results? The purpose of this study was to (1) assess the notable feelings experienced by non-incarcerated partners and (2) understand the implications of these feelings. Semi-structured interviews were conducted with 10 female participants who had their partners incarcerated at Nigeria’s Agodi-Ibadan Medium Correctional Facility. An interpretative phenomenological approach was employed to analyse their lived experience with Satir’s model. Thirteen sub-themes derived from feelings revealed the participants’ frustration, pain, and hurt; betrayal and anxiety; anger, confusion, and interruption; hostility, hunt, and fear; sadness, shame, and humiliation; being depressed and incarcerated; being surprised and in denial; being confused and helpless; being sorry and suffering double losses; being controlled as well as feeling relieved. This study found that 40% of participants felt frustrated, angry, interrupted, and hunted, while 30% felt hurt, bitter, or humiliated, and 20% felt betrayed, incarcerated, in denial, confused, or had a sense of relief while their partners were incarcerated. These experiences intensified the impacts of their partners’ incarceration. The study has recommendations for marriage and family specialists.